Morphosyntactic Features of Verbs in the South Morava Dialect of the Vlasotince Area - Stanković, Stanislav R. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The Prizren-Timok dialects of the Vlasotince area have yet not been systematically analyzed from a morphosyntactic perspective. This paper presents the first attempt to examine the verbal features of one of the three highly Balkanized idioms in this respect. The analysis of verb forms in the local South Morava speech confirms its affiliation with the broader Prizren–South Morava group and shows that, at the morphosyntactic level, they possess the vast majority of characteristics typical of the highly Balkanized area of the Serbian diasystem.